Open tibial pilon fractures: treatment with ankle-spanning Ilizarov fixator - Şahin, Ercan; Kalem, Mahmut (The European Research Journal, 2018)
Objective. The aim of this retrospective study was to report the treatment results obtained with the ankle-spanning Ilizarov fixator technique in the treatment of complex OTA/AO type 43C3 open tibial pilon fractures. Methods. A total of 14 patients with open OTA/AO type 43C3 tibial pilon fractures were evaluated. The demographics and fracture characteristics, preoperative and postoperative radiological evaluations, duration of follow-up (months), time to union (months) and complications were recorded. After collection of operative data, patients were invited for functional and radiological outcome evaluation. American Orthopaedic Foot and Ankle Society (AOFAS) scores and range of movement (ROM) of the ankle joint were investigated. Also radiologically the ankle osteoarthritis level according to the Bargon et al. criteria was noted. Results. The mean age of the patients was 48.7 years (range, 26-72 years). The mean follow-up period was 32 months (range, 25-46 months). The clinical and radiological time to union was mean 6.5 months (range, 5-11 months). On the postoperative ankle CT images, the separation within the ankle was measured as < 2mm in all patients and in 3 patients, stepping was measured as > 2mm. Following removal of the external fixator, dorsiflexion was measured as mean 15.5° (range, 0°-23°) and plantar flexion as mean 26.14° (range, 13°-36°). The mean AOFAS was 80.35 (range, 56-92). Conclusion. Satisfactory results can be obtained with the Ilizarov external fixator passing the ankle in the permanent treatment of AO-43C3 type open tibial pilon fractures.